The Effectiveness of Productive ZIS Movements Based on Local Wisdom “Can Coins” Towards The Economy of The Society of Malang District - Vika Annisa Qurrata; Qurrotu Ayniy Ayniy; Riqa Aniqa Helma Alam (Trunojoyo University of Madura, 2022)
The purpose of this study is to determine the economic impact of the productive zakat infaq sodaqoh (ZIS) movement based on indigenous wisdom and the use of